Analysis of the Influence of Population and Unemployment on Economic Growth in Central Kalimantan (Proceeding of the International Conference on Economics, Accounting, and Taxation, 2025)
This study aims to investigate the empirical impact of population size and unemployment rates on economic growth in Central Kalimantan Province. The research focuses on the regional context of Central Kalimantan, utilizing a longitudinal dataset covering the eleven-year period from 2013 to 2024. To achieve the research objectives, the study employs quantitative analysis through the SPSS software package, utilizing multiple linear regression as the primary analytical tool to examine the relationship between the dependent variable (economic growth) and the independent variables (population and unemployment). The findings of the analysis reveal a divergent impact between the two independent variables. The results indicate that the population has a significant and positive influence on economic growth in Central Kalimantan during the 2013-2024 period, suggesting that demographic factors play a crucial role in regional expansion. Conversely, the unemployment rate was found to have no significant effect on economic growth within the same timeframe. Furthermore, the study conducted a comprehensive suite of classical assumption tests to ensure the validity and reliability of the statistical model. The results of these diagnostics confirm that the regression model adheres to the assumption of normality, shows no evidence of multicollinearity among the variables, and is free from symptoms of heteroscedasticity. Additionally, the analysis concludes that the model does not exhibit any issues related to autocorrelation. Consequently, the regression model is deemed statistically robust and appropriate for providing an accurate representation of the economic dynamics in Central Kalimantan.